A serial fluoroscopy-guided thrombolytic therapy of a mechanical tricuspid prosthetic valve thrombosis with low-dose and ultra-slow infusion of tissue-type plasminogen activator - Macit Kalcik; Ozan Mustafa Gürsoy; Mehmet Ali Astarcıoğlu; Mehmet Özkan (KARE Publishing, 2014)
Prosthetic valve thrombosis is a life-threatening complication that is seen most commonly in patients with left-sided prosthetic valves. However, mechanical tricuspid valves carry the highest risk of thrombosis of any cardiac valve. Thrombolysis has been performed successfully in right-sided prosthetic valve thrombosis and has been recommended as the first-line treatment in these patients. Although two-dimensional and real-time three-dimensional transesophageal echocardiography are the gold standard imaging modalities for the diagnosis of prosthetic valve thrombosis, right-sided prosthetic valves may not be evaluated precisely. This is a serious problem during the followup of patients who receive thrombolytic therapy for tricuspid valve thrombosis. Fluoroscopy is an alternative noninvasive imaging method that provides valuable information about leaflet motion and may be used for such cases with restricted leaflets. Herein, we report a case of tricuspid valve thrombosis who was managed with low-dose (25 mg) and ultra-slow (25 hours) infusion of tissue-type plasminogen activator under the guidance of serial fluoroscopy.